The Effectiveness of Wayground Media in Improving Students' Mathematical Critical Thinking Skills - Shafa Aulia Anwar; Desty Haswati; Rika Sukmawati (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2026)
This study is designed to test the effectiveness of Wayground learning media in improving the mathematical critical thinking skills of grade X students of SMA Muhammadiyah 2 Tangerang on the material of the Three-Variable Linear Equation System. The method used was a one-group pretest-posttest design, and purposive sampling of 24 students was selected in class X6. The instrument is in the form of 4 valid description questions that measure the critical thinking aspect. Data were analyzed by Kolmogorov-Smirnov normality test, paired sample t-test, and N-Gain using SPSS 26. The findings showed that the average pretest score of 37.2 (SD = 6.7) increased to 51.9 (SD = 5.1). The Kolmogorov–Smirnov normality test yielded a value of Sig. = 0.1 (> 0.05), so that the data was declared to be normally distributed; The paired sample t-test showed t = –11.5 (Sig. = 0.0 < 0.05) which means there was a significant improvement. The homogeneity test was not applied because the analysis involved only one group (pretest–posttest) without a comparison between groups that required a variance homogeneity test. An average N-Gain of 0.5 (medium category) indicates that Wayground is quite effective, but has not yet reached the high effectiveness category; This means that a significant increase in scores occurs, but the impact is still at a moderate level and needs additional media support or strategies to further increase effectiveness.